The Penerapan QoS (Quality Of Service) Dalam Menganalisis Kualitas Kinerja Jaringan Komputer (Studi Kasus Hotel Maxone Palembang) - Mahmud Mahmud; Yarza Aprizal (Journal of Information System Research (JOSH), 2022)
MaxOne Hotel Palembang has a computer network that connects every device. A good network is reflected in the quality provided to its users. Computer networks and the internet become a necessity that can’t be separated when MaxOne Palembang Hotel runs its business processes, of course this results in higher tasks received by the network, therefore activities are needed to ensure the quality of the computer network network at MaxOne Hotel Palembang. This research applies the steps of action research method by applying the calculation of Quality of Service (QoS) with 4 (four) parameters, They are Throughput, Packet Loss, Delay and Jitter with Wireshark as a tool for measurement. After the measurement results are obtained, they will be compared with the quality standards of the computer networks its Telecommunications and Internet Protocol Harmonization Over Networks (TIPHON). The results of this research show the average throughput is 81.76%, packet loss is 2%, Delay is 0.432 ms, Jitter is 0.42 ms. The conclusion is the quality of the computer network and internet at the MaxOne Hotel Palembang from all the parameters used shows an index of 3.81 which means it is very satisfying.